“…been down so long…”: perpetual vs. intermittent inferiority and the Köhler group motivation gain in exercise groups - Kerr, Norbert L.; Forlenza, Samuel T.; Irwin, Brandon C.; Feltz, Deborah L. (My University, 2013)
Prior research has documented the Köhler motivation gain effect-- working with a more capable partner at a task that makes one’s performance indispensible for the group can boost task motivation. Recent research has shown that the Köhler effect can boost one’s persistence exercising in groups, but that always being the group’s “weak link” can eventually undermine these motivation gains. An experiment is reported which contrasts having a partner that is more capable on all/both exercise tasks with one that is more capable on the focal task, but inferior on the second task. The Köhler effect on the focal task was replicated and unmoderated by the uniformity of the partner’s exercise superiority. Implications for further research and application are discussed.
Keywords: Köhler effect; Inferiority; Exercise groups; Motivation